Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
All Days 2012
DOI: 10.2118/160016-ms
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a CO2 Foam Pilot Study in the SACROC Field: Performance Evaluation

Abstract: A new conformance solution has been developed to help producers reach and recover more oil from existing wells while simultaneously reducing operating expenditures. This new technology successfully addresses shortcomings associated with existing miscible gas EOR (enhanced oil recovery) processes by generating foams of supercritical CO 2 fluid and water in the formation which alter mobility and improve vertical conformance. Ultimately, the process can improve the profitability of existing wells by enhancing res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 11 publications
2
42
0
Order By: Relevance
“…Foam possesses enormous potential in enhanced oil recovery (EOR) (Farajzadeh, Andrianov, Bruining, & Zitha, ; Kovscek & Radke, ; Talebian, Tan, Sagir, & Muhammad, ; Turta & Singhal, ). Foam integrates the advantages of both gas and surfactant, which has been considered as one of the most efficient displacement fluids in EOR (Enick, Olsen, Ammer, & Schuller, ; Li, Le Bleu, Liu, Hirasaki, & Miller, ; Sanders et al, ; Tang et al, ). The successful application of foam in the field is determined by the foam behavior to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…Foam possesses enormous potential in enhanced oil recovery (EOR) (Farajzadeh, Andrianov, Bruining, & Zitha, ; Kovscek & Radke, ; Talebian, Tan, Sagir, & Muhammad, ; Turta & Singhal, ). Foam integrates the advantages of both gas and surfactant, which has been considered as one of the most efficient displacement fluids in EOR (Enick, Olsen, Ammer, & Schuller, ; Li, Le Bleu, Liu, Hirasaki, & Miller, ; Sanders et al, ; Tang et al, ). The successful application of foam in the field is determined by the foam behavior to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…In Le et al (2008), experimental and field scale simulation results show this is the most promising injection scenario which gave highest oil recovery and injectivity. Field trials indicated a 30% sweep efficiency improvement (Sanders et al 2012). Supercritical carbon dioxide (scCO 2 ) with its easily attainable critical temperature and pressure (31.1°C and 7.38 MPa) can be viewed as an ideal chemical processing solvent because it is nontoxic, inexpensive, volatile, nonflammable, readily available in large quantities, and environmentally benign (Eastoe et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Either liquid or CO 2 phase could be used to delivery those novel surfactants. A field trial was carried out in west Texas using surfactant injection in the CO 2 phase to create a CO 2 -in-water emulsion or foam to improve vertical conformance and create in-depth mobility control (Sanders et al 2012). Results indicated a 30% CO 2 trapping improvement in situ.…”
Section: Introductionmentioning
confidence: 99%
“…While there have been several successful foam pilots (see e.g. (Blaker et al, 2002;Li et al, 2009;Mukherjee et al, 2014;Sanders et al, 2012;Yu et al, 2008), historically very few foam pilots in fractured reservoirs have been performed, and those few have largely been deemed unsuccessful (Enick et al, 2012;Smith, 1988). This has been attributed to the lack of foam generation mechanisms in fractures, namely snap-off, film division and leave-behind.…”
Section: Introductionmentioning
confidence: 99%